The influence of cement morphology parameters on the strength of the cement-bone interface in tibial tray fixation - Nagel, Katrin; Bishop, Nicholas; Schlegel, Ulf J.; Püschel, Klaus; Morlock, Michael (The journal of arthroplasty, 2017)
Background: The strength of the cement-bone interface in tibial component fixation depends on the morphology of the cement mantle. The purpose of this study was to identify thresholds of cement morphology parameters to maximize fixation strength using a minimum amount of cement. Methods: Twenty-three cadaveric tibiae were analyzed that had been implanted with tibial trays in previous studies and for which the pull-out strength of the tray had been measured. Specimens were separated into a group failing at the cement-bone interface (INTERFACE) and one failing in the bulk bone (BULK). Maximum pull-out strength corresponds to the ultimate strength of the bulk bone if the cement-bone interface is sufficiently strong. 3D models of the cement mantle in situ were reconstructed from computed tomography scans. The influences of bone mineral density and 6 cement morphology parameters (reflecting cement penetration, bone-cement interface, cement volume) on pull-out strength of the BULK group were determined using multiple regression analysis. The threshold of each parameter for classification of the specimens into either group was determined using receiver operating characteristic analysis. Results: Cement penetration exceeding a mean of 1.1 mm or with a maximum of 5.6 mm exclusively categorized all BULK bone failure specimens. Failure strength of BULK failure specimens increased with bone mineral density (R2 = 0.67, P < .001) but was independent of the cement morphology parameters. Conclusion: To maximize fixation strength, a mean cement penetration depth of at least 1.1 mm should be achieved during tibial tray cementing.